Diabetes mellitus among arsenic exposed and non-exposed young adults in Bangladesh - Khan, Manzurul Haque; Chanda, Bipul K.; Ahmad, Sk Akhtar (International Journal Of Community Medicine And Public Health, 2016)
Background: Studies in different countries including Bangladesh have found association with arsenic exposure and diabetes mellitus. However, the occurrence of diabetes mellitus amongst the arsenic exposed young adults, remains to be elaborately explored. This study was carried out among the arsenic exposed young adults to assess their glycaemic status. Methods: This was a cross sectional comparative study carried out among the arsenic exposed and non-exposed young adults aged 30 to 39 years. Results: Among the total 1546 respondents, arsenic exposed respondents were 1043(67.5%) and non-exposed respondents were 503 (32.5%). Of the arsenic exposed respondents 494 (47.4%) were suffering from arsenicosis. The arsenic exposed respondents were found to suffer more from DM (5.6%) and IGT (23.0%) compared to those of non-arsenic exposed respondents and the difference was highly significant (χ2= 30.470; p=0.000). While comparing DM and IGT between arsenicosis and non-arsenicosis respondents, significantly (χ2=12.989; p=0.002) a higher proportion of the arsenicosis respondents were found to suffer from DM (7.9%) and IGT (24.9%). Multinomial regression analysis showed, DM and IGT were 3.6 times and 2.5 times more likely to develop among the young adults having arsenicosis compared to those of non-exposed young adults. Conclusions: The study revealed that the arsenic exposed population is at high risk of developing diabetes and IGT in their early adult hood. Among the arsenicosis young adults the situation is more threatening; the prevalence is more than twice compared to that of arsenic non-exposed young adults.